2012
DOI: 10.1002/cae.20430
|View full text |Cite
|
Sign up to set email alerts
|

Control of dissolved oxygen concentration using neural network in a batch bioreactor

Abstract: ABSTRACT:Artificial neural networks (ANN) have been utilized for many chemical applications because of their ability to learn system features. This paper presents the use of feedforward neural networks for dynamic modelling and dissolved oxygen (DO) control of a batch yeast fermentation. The ARMAX model of this nonlinear process is also presented. Model verification is tested by using experimental data. Different ANNs are trained using the backpropagation learning algorithm. The resulting ANNs are introduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Conventional strategies in aerobic processes are essentially based on measurements of the dissolved oxygen concentration (DOC), which is then controlled by adjusting the stirrer speed and, occasionally, the composition of the gas supplied to the reactor (for instance, enrichment with pure oxygen) or the total gas flow rate [2, 3]. Some improvements have been made over time including more refined DOC controls through the use of mechanistic models [3] or neural networks [4], to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional strategies in aerobic processes are essentially based on measurements of the dissolved oxygen concentration (DOC), which is then controlled by adjusting the stirrer speed and, occasionally, the composition of the gas supplied to the reactor (for instance, enrichment with pure oxygen) or the total gas flow rate [2, 3]. Some improvements have been made over time including more refined DOC controls through the use of mechanistic models [3] or neural networks [4], to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…ANN provide to learn system properties of many chemical applications. Although the history of ANN is old, studies have shown how neural networks can be used for classification, estimation and prediction of bioprocesses since the late of 1980s 10,16) . The structure of ANN, consisting of layers made of neurons, simulates the functioning of human brain 15) .…”
Section: Discussionmentioning
confidence: 99%
“…The structure of ANN, consisting of layers made of neurons, simulates the functioning of human brain 15) . There are many neural network applications in bioprocesses, such as surface roughness, surface hardness and wear prediction of materials 10) . However, no research on the surface roughness and hardness prediction model of dental materials has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demonstrations of the performances of classical controllers (such as PID controllers in this study) on the electromechanical system can be given in undergraduate automatic control theory courses for aerospace engineering major at Beihang University School of Astronautics. It should be noted that the controller is open for development, and many advanced control approaches (sliding mode control , fuzzy control , and neural network control ) can be studied in the future by using the proposed HIL simulation system HIL‐GSS . On the other hand, HIL‐GSS can also serve as an experiment setup for graduate level courses (missile guidance theory and parameter identification ) at Beihang University School of Astronautics.…”
Section: Discussionmentioning
confidence: 99%